Asymmetric dimethylarginine induces maladaptive function of the blood-brain barrier - Buzhdygan, Tetyana P.; Ramirez, Servio H.; Nenov, Miroslav N. (Frontiers in Cell and Developmental Biology, 2024)
Growing body of evidence suggests that cardiovascular risk factor, asymmetric dimethylarginine (ADMA), can be implicated in the pathogenesis of neurodegenerative and psychiatric disorders. In part, ADMA can affect brain health negatively modulating critical functions of the blood-brain barrier (BBB). The precise mechanisms and consequences of ADMA action on the cerebral vasculature remains unexplored. Here, we evaluated ADMA-induced maladaptation of BBB functions by analyzing real time electrical cell-substrate impedance, paracellular permeability, immune-endothelial interactions, and inflammatory cytokines production by primary human brain microvascular endothelial cells (hBMVEC) treated with ADMA. We found that ADMA disrupted physical barrier function as evident by significant decrease in electrical resistance and increase in paracellular permeability of hBMVEC monolayers. Next, ADMA triggered immune-endothelial interactions since adhesion of primary human monocytes and their extravasation across the endothelial monolayer both were significantly elevated upon treatment with ADMA. Increased levels of cell adhesion molecules (VCAM-1 and RANTES), VEGF-A and inflammatory cytokines (IL-1β, TNF-α, IL-6, IL-10, IL-4, IL-2, IL-13, IL-12p70) characterize ADMA-induced hBMVEC dysfunction as inflammatory. Overall, our data suggest that ADMA can impair BBB functions disrupting the endothelial barrier and eliciting neuroinflammatory and neuroimmune responses.